2022
DOI: 10.1124/dmd.122.000858
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nuclear Receptors PXR and CAR by Small Molecules and Signal Crosstalk: Roles in Drug Metabolism and Beyond

Abstract: Pregnane X receptor (PXR) and constitutive androstane receptor (CAR) are ligand-activated transcription factors that regulate the expression of drug metabolizing enzymes and drug transporters. Since their discoveries, they have been studied as important factors for regulating processes related to drug efficacy, drug toxicity, and drug-drug-interactions. However, their vast ligand-binding profiles extend into additional spaces, such as endogenously produced chemicals, microbiome metabolites, dietary compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…A recent review has summarized a journey of rewards of xenobiotic receptors for their discovery stories (Xie, 2022). PXR and CAR are transcription factors and have since been defined as master regulators of xenobiotic responses through their transcriptional regulation of drug-metabolizing enzymes and transporters, including CYPs (Poudel et al, 2022). Activation of PXR and CAR is also associated with the development of numerous metabolic diseases (Zhang et al, 2022).…”
Section: Induction Of Cyp Expression By Drugs Through Activation Of X...mentioning
confidence: 99%
“…A recent review has summarized a journey of rewards of xenobiotic receptors for their discovery stories (Xie, 2022). PXR and CAR are transcription factors and have since been defined as master regulators of xenobiotic responses through their transcriptional regulation of drug-metabolizing enzymes and transporters, including CYPs (Poudel et al, 2022). Activation of PXR and CAR is also associated with the development of numerous metabolic diseases (Zhang et al, 2022).…”
Section: Induction Of Cyp Expression By Drugs Through Activation Of X...mentioning
confidence: 99%
“…PXR also exhibits antiinflammatory and anti-fibrosis effects in the intestines 30 . Meanwhile, CAR, through a different protective mechanism, facilitates BA detoxification in the hepatocytes of CA-treated mice with Fxr and Pxr deficiencies 31,32 . CAR also functions locally in intestinal CD4 + effector T cells, by contributing to BA detoxification and inflammation resolution by upregulating the anti-inflammatory cytokine interleukin (IL)-10 and BA-detoxifying enzymes and transporters 25 .…”
Section: Ba Receptorsmentioning
confidence: 99%
“…NPs have also been reported as highly effective activators not only of rodent Constitutive Androstane Receptor (CAR, NR1I3) but also of human and rodent Pregnane X Receptor (PXR, NR1I2). CAR is one of the main drug- and xenobiotic-responsive transcription factors regulating the expression of detoxification enzymes, conjugation enzymes, and transporters involved in the elimination of endogenous and exogenous substances, such as bilirubin, bile acids, and xenobiotics. , Additionally, CAR has an important role in glucose and lipid metabolism, as well as in endobiotic metabolism of steroid hormones, , and its modulation may offer therapeutic intervention in some metabolic diseases . Many environmental toxicants or industrial chemicals as well as some drugs have been identified as CAR activators …”
Section: Introductionmentioning
confidence: 99%
“…6,12 Additionally, CAR has an important role in glucose and lipid metabolism, as well as in endobiotic metabolism of steroid hormones, 13,14 and its modulation may offer therapeutic intervention in some metabolic diseases. 15 Many environ-mental toxicants or industrial chemicals as well as some drugs have been identified as CAR activators. 16 CAR has a typical nuclear receptor structure consisting of the DNA-binding domain (DBD) connected to the ligandbinding domain (LBD, Figure 1A,B) via a hinge region.…”
Section: Introductionmentioning
confidence: 99%